Routing Algorithm for DTN Based on Congestion Control - Song Ningning; Liu Qian; Zhou Xianwei; Xue Peipei (Institute of Advanced Engineering and Science, 2013)
Different from Internet networks, DTN has its own unique characteristics, like intermittent connectivity, low data transfer rate, high latency and limited storage and node resources. Routing technology is always the key to DTN research. In this paper, a routing protocol that is PNCMOP was proposed. It makes some improvement of Epidemic routing protocol, and also to decrease the end-to-end average delay and improve delivery ratio, especially with congestion control. Simulation results show that PNCMOP achieved a good performance. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3348